Successful adalimumab treatment and usefulness of capsule endoscopy for gut inflammation concomitant with ankylosing spondylitis. Issue 4 (4th July 2019) - Ota, Shinji; Sakuraba, Hirotake; Hiraga, Hiroto; Hasui, Keisuke; Satake, Miwa; Hanabata, Norihiro; Akemoto, Yui; Watanabe, Rina; Tanaka, Nahoko; Ishiguro, Yoh; Tanaka, Masanori; Fukuda, Shinsaku
Abstract: Here we describe a 20-year-old man with ankylosing spondylitis and gut inflammation, who was successfully treated with adalimumab. Capsule endoscopy and ileocolonoscopy showed multiple erosions and aphthoid ulcers in the ileum and the ileocecal valve. Immunohistochemical analysis of the terminal ileum demonstrated that the number of IL-23p19 expressing macrophages was increased. Adalimumab was administered, and his back pain and abdominal symptoms improved. Adalimumab might be an effective treatment for gut inflammation related to ankylosing spondylitis.